A revised typification of Jasione corymbosa and J. glabra (Campanulaceae) from the Western Mediterranean area - Ferrer-Gallego, Pedro Pablo; Romo, Ángel; Roselló, Roberto; Laguna, Emilio; Peris, Juan Bautista (Phytotaxa, 2015)
The genus Jasione Linnaeus (1753: 163) (Campanulaceae Juss.) is represented by ca. 16 species distributed throughout Europe and the Mediterranean Region, from coastal dunes to alpine zones, and growing on a wide variety of substrates as well (Sales & Hedge 2001b). The genus shows a high degree of polymorphism, which can be partially caused by its representation accross a wide range of ecological niches. This variability reaches its maximum expression within the Iberian Peninsula (Bokhari & Sales 2001).